Genetic (co)variation between resistance to Aeromonas hydrophila and growth in tambaqui (Colossoma macropomum) - Ariede, Raquel B. [UNESP]; Freitas, Milena V. [UNESP]; Agudelo, John F.G. [UNESP]; Borges, Carolina H.S. [UNESP]; Lira, Lieschen V.G. [UNESP]; Yoshida, Grazyella M.; Pilarski, Fabiana [UNESP]; Yáñez, José M.; Hashimoto, Diogo T. [UNESP] (Elsevier, 2020)
Tambaqui (Colossoma macropomum) is the main native fish farmed in South American continental aquaculture. One of the major pathogens affecting world fresh water aquaculture is the bacterium Aeromonas hydrophila, which generates several disease outbreaks and production losses in farmed tambaqui stocks. Up to date, there are no studies focusing on understanding the quantitative basis for the genetic improvement for disease resistance in tambaqui. Thus, the objective of this study was to determine the genetic parameters for resistance to A. hydrophila and the genetic correlation with average daily gain in juveniles of tambaqui, to determine whether these traits can be included in selective breeding programs. Estimation of genetic parameters was performed using data from an experimental challenge performed in 18 full-sib families, using a total of 576 individuals. Before bacterial challenge, all animals were evaluated for average daily gain (ADG) in the juvenile phase during 30 days. The challenge spanned 120 h (5 days) and disease resistance traits were defined as: i) binary survival (BS) and, ii) time of death (TD) of fish presenting clinical signs of A. hydrophila infection. The mean ADG was 0.49 g/day (SD = 0.21) in the population and heritability for this trait was moderate (h2 = 0.37 ± 0.13). BS and TD varied considerably among families (26% to 89% and 10.7 h to 69.2 h, respectively), which indicated a significant genetic variation related to resistance to A. hydrophila infection. Low to moderate values for heritability were found for BS and TD (0.17 ± 0.06 and 0.23 ± 0.09, respectively). The genetic correlations between resistance to A. hydrophila and ADG in juveniles of tambaqui were not significantly different from zero. The significant genetic variation found for A. hydrophila resistance in tambaqui indicates that selecting superior genotypes is a viable approach to reducing the impact of diseases outbreaks in aquaculture.
Keywords: Aeromoniosis; Disease resistance; Genetic parameters; Heritability